Efficacy of physical activity shared between parents and children to improve sports initiation in the M.A.M.I.deporte® program - Belén Cueto-Martín; Juan Carlos De la Cruz-Márquez; Rafael Burgueño-Menjíbar; Eduardo García-Mármol (Frontiers Media S.A., 2024)
ObjectiveTo determine if the active methodology for improving sports initiation (M.A.M.I.deporte®) shared between children and parents successfully promotes children in sports activities, maintains their activity and improves long-term adherence.ParticipantsThe study involved 118 participants aged between 2 and 11 years (6.3 ± 2.3). In the first season, 34 participated (16 girls; 18 boys); in the second season, 46 participated (22 girls; 24 boys) and in the third season, 38 participated (19 girls; 19 boys).MethodologyIt was carried out from October to June over three academic years for two hours a week. Every 4 sessions a different sporting activity was carried out, planned so that parents and children could practise them, simultaneously.AnalysisAt the beginning and end of each period, a survey was carried out on the sports activities in which the participants had started. If participants remained in the activity, the survey was face-to-face and if participants no longer attended the activity, they were contacted by telephone. Descriptive values were obtained for the variables in absolute and percentage form and a repeated measures anova was performed.ResultsVigorous physical activity performed was 3.82 ± 1.16 h/week in the first year, 3.38 ± 1.59 in the second year and 2.99 ± 1.46 in the third year with no significant differences between any of the years. 32.20% joined other sporting activities and only 6.78% gave up vigorous physical activity.ConclusionJoint activity of parents and children contributed to maintaining vigorous physical activity at the recommended levels in the child population with only 6.78% (n = 8) of the participants dropping out.